Representation of Interpersonal Communication Patterns in the Podcast by Deddy Corbuzier “Log In episode 15” - Mochammad Robi Ardiansyah Supiatun; Sufyanto Sufyanto (Indonesian Journal of Cultural and Community Development, 2023)
This qualitative research aims to analyze the interpersonal communication patterns in Deddy Corbuzier's podcast, specifically focusing on "Log in Episode 15". The study explores how open communication and appropriate perspectives contribute to effective interpersonal communication. Using a semiotic analysis method, data collection involves observation, relevant previous research, and case studies to strengthen the findings. The researcher examines the signs within the podcast episode and interprets them to draw conclusions. The results depict diverse interpersonal communication patterns influenced by various social backgrounds and held values. This research highlights the importance of understanding and adapting to different communication styles, enabling more effective and meaningful interactions. Highlights: Varied communication patterns: The study uncovers diverse interpersonal communication patterns within Deddy Corbuzier's podcast, emphasizing the influence of social backgrounds and personal values on communication styles. Semiotic analysis: The research utilizes a semiotic analysis method to examine the signs and symbols present in the podcast episode, providing insights into the underlying meanings and interpretations of communication within the context of the podcast. Effective communication strategies: The findings highlight the importance of open communication and adopting appropriate perspectives for effective interpersonal communication, underscoring the significance of understanding different communication styles in fostering meaningful interactions. Keywords: Interpersonal communication, Podcast, Deddy Corbuzier, Semiotic analysis, Communication patterns